Adult learners' satisfaction towards iclass system among students with difference level of self-regulated learning / Marliana Baharudin - Baharudin, Marliana (2011)
This study explores the adult learners' satisfaction toward the i-Class system provided by UiTM. Using a random sampling method, 440 students from a population of more than 1000 distance learning students in UiTM Shah Alam, Selangor were selected. The population of this study included students with degrees in Electronic Distance Learning Education (e-PJJ) students. The need to study the level of students' satisfaction on i-Class system is important in order to provide a successful learning environment for all Electronic Distance Learning Education (e-PJJ) students. It is hoped that this study could provide us some solution to ensure students satisfaction with management systems in UiTM. The questionnaire as an instrument in this study was adapted from 'Interactivity in Distance Learning: The Digital and students Satisfaction' by Irons, et al. (2002). Descriptive analysis and correlation analysis were used to analyze the mean and frequency and the correlation between the variables in this study. The results indicated that level of students' satisfaction was moderate. There was negative relationship between ways of accessing the i-Class system and the level of students' satisfaction towards the i-Class system. Therefore, there is no relationship between student's preference to use the i-Class system and the level of students' satisfaction. On the other hand, there was relationship between overall mean for self-regulated learning and the level of students' satisfaction towards the i-Class system. In addition, further analysis were done to investigate the relationship between level of students' satisfaction with every areas consists in self-regulated learning survey. All those areas were cognitive metacognitive, resources management strategies, effort regulation, peer learning, and last but not least, peer seeking. However, only effort regulation, peer learning, and help seeking were correlated with correlated with all self-regulated learning's areas. Finally, implication of the research, recommendations to increase level of students' satisfaction towards the i-Class system, recommendations for future research was presented in previous sections accordingly.